Perbaikan Sistem Lokalisasi Komponen Impor Studi Kasus di PT TMMIN - Victor Chiarouven; I Nyoman Sutapa (Jurnal Titra, 2020)
PT Toyota Motor Manufacturing Indonesia (PT TMMIN) is an automotive manufacturing company and also exporter of Toyota cars and car components. Cars are made from a variety of components that are supplied from domestic (local) and abroad (imported). The import component has negative impact on PT TMMIN’s revenue. The negative impacts are due to IDR exchange rate against the US Dollar which tends to weaken from year to year. Localization of imported components is done to reduce the impact of purchases with foreign currency. The localization process is carried out by forex strategic localization team with manual document process. The manual process takes long time. The analysis process for solving problems using DMAIC approach. The improvement solution is done by designing a macro-VBA program. This improvement reduces process lead time, the decrease occurred between 88,57% to 98,47%. This improvement shows that macro-VBA have a significant impact on the time reduction.